Trend in childhood obesity reflects socioeconomic status in Argentina - Alicia B. Orden; Muriel S. Lamarque; María C. Apezteguía (Taylor & Francis Group, 2019)
Background: Surveillance of childhood obesity is essential to guide preventive policies and interventions. Aim: To analyse trends in overweight and obesity by socioeconomic status (SES) in Argentinian schoolchildren during the last decade. Subjects and methods: Two cross-sectional studies in schoolchildren aged 6-12 years were compared. The first study was conducted in 2005/07 (n = 1418) and the second one in 2015/16 (n = 1366). Overweight and obesity were estimated by the International Obesity Task Force (IOTF) cut-offs. The type of school (public/private) and parental education level were used as measures of SES. Data were analysed by linear and logistic regression with survey year, type of school, parental education level, and sex as independent variables. Results: From 2005 to 2016 overweight and obesity increased by 7.3% and 5.0%, respectively. The change was significantly higher in boys (9.6% and 8.3%) and girls (9.6% and 5.4%) from public schools, and in children whose fathers had low (10% and 8.3%) and middle (9.0% and 5.5%) education levels. No significant changes were found in children attending private school or those whose fathers had a higher education level. Conclusions: Obesity is still increasing in this population. SES disparities are strongly associated with this trend, with stabilisation in children from high SES.